Expression of Foxm1 Transcription Factor in Cardiomyocytes Is Required for Myocardial Development - Bolte, Craig (Public Library of Science, 2011)
Forkhead Box M1 (Foxm1) is a transcription factor essential for organ morphogenesis and development of various cancers. Although complete deletion of Foxm1 in Foxm1(−/−) mice caused embryonic lethality due to severe abnormalities in multiple organ systems, requirements for Foxm1 in cardiomyocytes remain to be determined. This study was designed to elucidate the cardiomyocyte-autonomous role of Foxm1 signaling in heart development. We generated a new mouse model in which Foxm1 was specifically deleted from cardiomyocytes (Nkx2.5-Cre/Foxm1(fl/f) mice). Deletion of Foxm1 from cardiomyocytes was sufficient to disrupt heart morphogenesis and induce embryonic lethality in late gestation. Nkx2.5-Cre/Foxm1(fl/fl) hearts were dilated with thinning of the ventricular walls and interventricular septum, as well as disorganization of the myocardium which culminated in cardiac fibrosis and decreased capillary density. Cardiomyocyte proliferation was diminished in Nkx2.5-Cre/Foxm1(fl/fl) hearts owing to altered expression of multiple cell cycle regulatory genes, such as Cdc25B, Cyclin B(1), Plk-1, nMyc and p21(cip1). In addition, Foxm1 deficient hearts displayed reduced expression of CaMKIIδ, Hey2 and myocardin, which are critical mediators of cardiac function and myocardial growth. Our results indicate that Foxm1 expression in cardiomyocytes is critical for proper heart development and required for cardiomyocyte proliferation and myocardial growth.